Implementing the United Kingdom's ten-year teenage pregnancy strategy for England (1999-2010): How was this done and what did it achieve?. Issue 1 (December 2016) - Hadley, Alison; Ingham, Roger; Chandra-Mouli, Venkatraman
Abstract Background In 1999, the UK Labour Government launched a 10-year Teenage Pregnancy Strategy for England to address the country's historically high rates and reduce social exclusion. The goal was to halve the under-18 conception rate. This study explores how the strategy was designed and implemented, and the features that contributed to its success. Methods This study was informed by examination of the detailed documentation of the strategy, published throughout its 10-year implementation. Results The strategy involved a comprehensive programme of action across four themes: joined up action at national and local level; better prevention through improved sex and relationships education and access to effective contraception; a communications campaign to reach young people and parents; and coordinated support for young parents (The support programme for young parents was an important contribution to the strategy. In the short term by helping young parents prevent further unplanned pregnancies and, in the long term, by breaking intergenerational cycles of disadvantage and lowering the risk of teenage pregnancy.). It was implemented through national, regional and local structures with dedicated funding for the 10-year duration. The under-18 conception rate reduced steadily over the strategy's lifespan. The 2014 under-18 conception rate was 51% lower than the 1998 baseline and there have been significant reductions in areas of high deprivation. One leading social commentator described the strategy as 'The success story of our time' (Toynbee, The drop in teenage pregnancies is the success story of our time, 2013). Conclusions As rates of teenage pregnancy are influenced by a web of inter-connected factors, the strategy was necessarily multi-faceted in its approach. As such, it is not possible to identify causative pathways or estimate the relative contributions of each constituent part. However, we conclude that six key features contributed to the success: creating an opportunity for action; developing an evidence based strategy; effective implementation; regularly reviewing progress; embedding the strategy in wider government programmes; and providing leadership throughout the programme. The learning remains relevant for the UK as England's teenage birth rate remains higher than in other Western European countries. It also provides important lessons for governments and policy makers in other countries seeking to reduce teenage pregnancy rates.